Chemical State of Nitrogen and Visible Surface and Schottky Barrier Driven Photoactivities of N-Doped TiO2 Thin Films. - Romero-Gómez, Pablo; Rico, Victor; Borrás, Ana; Barranco, Ángel; Espinós, Juan Pedro; Cotrino, José; González Elipe, Agustin (ACS, 2009)
N-doped TiO2 thin films have been prepared by plasma enhanced chemical vapor deposition and by physical vapor deposition by adding nitrogen or ammonia to the gas phase. Different sets of N-doped TiO2 thin films have been obtained by changing the preparation conditions during the deposition. The samples have been characterized by X-ray diffraction, Raman, UV−vis spectroscopy, and X-ray photoemission spectroscopy (XPS). By changing the preparation conditions, different structures, microstructures, and degrees and types of doping have been obtained and some relationships have been established between these film properties and their visible light photoactivity. The N1s XP spectra of the samples are characterized by three main features, one tentatively attributed to Ti−N (i.e., nitride with a binding energy (BE) of 396.1 eV) and two others with BEs of 399.3 and 400.7 eV, tentatively attributed to nitrogen bonded simultaneously to titanium and oxygen atoms (i.e., Ti−N−O like species). By controlling the deposition conditions it is possible to prepare samples with only one of these species as majority component. It has been shown that only the samples with Ti−N−O like species show surface photoactivity being able to change their wetting angle when they are illuminated with visible light. The presence of these species and an additional complex structure formed by a mixture of anatase and rutile phases is an additional condition that is fulfilled by the thin films that also present photocatalytic activity with visible light (i.e., surface and Schottky barrier driven photoactivities). The relationships existing between the reduction state of the samples and the formation of Ti−N or Ti−N−O like species are also discussed.
https://openpolicyfinder.jisc.ac.uk/id/publication/7799
Keywords: Películas delgadas; Materiales nanoestructurados; Tio2; Photoactivity; Thin films; Nanomaterials